Surface hydroxylation flexible MOFs (Metal-Organic Frameworks) material, preparation method and application
The surface hydroxylation is directly performed during the synthesis process by water/solvent thermal synthesis method, which solves the problem of insufficient brittleness and thermal stability of traditional MOFs materials, and prepares high-performance flexible MOFs materials, achieving efficient storage and transportation of natural gas.
Patent Information
- Application Number
- CN202510355286.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional MOFs materials have problems such as high brittleness and insufficient thermal stability. The existing preparation methods have defects such as high energy consumption, easy introduction of impurities, and complex processing, which is difficult to meet the needs of wet natural gas storage.
The water/solvent thermal synthesis method is used to combine the basic framework synthesis and surface hydroxylation treatment of MOFs materials into one step, and directly hydroxylation is performed during the synthesis process, simplifying the production process and improving product yield and purity.
Flexible MOFs materials with high specific surface area, adjustable pore structure and hydroxyl-rich surface were prepared, which improved its performance and application range and achieved efficient storage and transportation of natural gas under mild conditions.
Smart Images

Figure CN119875140A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of MOFs materials, and in particular to a surface hydroxylated flexible MOFs material, a preparation method and an application thereof. Background Art
[0002] At present, most gas fields are not suitable for liquefied natural gas (LNG) and pipeline transportation (PNG) due to their small scale and distance from the natural gas pipeline network. In response to the urgent need for high-density storage and transportation of natural gas in small-scale gas fields, wet natural gas storage technology provides a new solution for the storage and transportation of natural gas. Wet natural gas storage technology stores natural gas in a water-containing environment through porous media, such as activated carbon, MOFs materials and silica gel, and achieves efficient storage of natural gas with the help of the nano-confinement effect of porous media. Porous media not only adsorb natural gas, but also provide contact area and nucleation sites for hydrate formation, improve the hydrate formation kinetics, and thus increase natural gas reserves. However, as reserves increase, the heat of adsorption and the heat of hydrate formation react on the storage process, inhibiting further increases in reserves.
[0003] Traditional MOFs materials have problems such as high brittleness and insufficient thermal stability; the existing preparation methods of MOFs materials have the following defects: First, the brittleness problem. MOFs materials synthesized by traditional methods are fragile due to crystal structure defects and are difficult to meet the needs of wet natural gas storage; second, the synthesis efficiency is low, the reaction temperature is too high or the time is too long, the energy consumption is high and impurities are easily introduced; third, the processing is complicated, there are many processing steps, and multiple acid washing or long drying are required, which affects the purity of the material; fourth, the application is limited, and its adaptability in the energy storage field has not been fully utilized. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a surface hydroxylated flexible MOFs material, a preparation method and an application. The surface hydroxylated flexible MOFs material has a high specific surface area, a controllable pore structure and a metal organic framework material rich in hydroxyl groups on the surface. The surface hydroxylation enhances the hydrophilicity and chemical reaction activity; the water / solvent thermal synthesis method is used to combine the two major steps of MOFs material basic skeleton synthesis and surface hydroxylation treatment into one step, and direct hydroxylation is carried out during the synthesis process, simplifying the production process and improving the product yield and purity; the surface hydroxylated flexible MOFs material can be applied to the field of natural gas storage.
[0005] On the one hand, an embodiment of the present invention provides a method for preparing a surface hydroxylated flexible MOFs material, comprising: Dissolve 5-10 mmol aluminum nitrate nonahydrate in 30 ml deionized water and stir until completely dissolved to obtain an inorganic aluminum salt solution; Dissolve 5-10 mmol 2-hydroxyterephthalic acid in 30 ml N,N-dimethylformamide and stir until completely dissolved to obtain an organic ligand solution; The organic ligand solution is dripped into the aluminum salt inorganic solution to form a mixed solution, and the mixed solution is transferred to a stainless steel high-pressure reactor to perform a crystallization reaction at 130-220° C. for 24-72 h; After the temperature of the reactor is cooled to room temperature, the MOFs material precipitate is obtained by centrifugation; Washing and centrifuging the MOFs material precipitate to remove residual organic matter and anhydrous ethanol precipitated on the surface of the MOFs material precipitate; The MOFs material precipitate is placed in a constant temperature drying oven and dried at 60-80° C. for 10-14 h to obtain a surface hydroxylated flexible MOFs material.
[0006] According to some embodiments of the present invention, the chemical formula of the surface hydroxylated flexible MOFs material is MIL-53(Al)-OH, the chemical formula of the aluminum nitrate nonahydrate is Al(NO3)39H2O, and the chemical formula of the 2-hydroxyterephthalic acid is H2BDC-OH.
[0007] According to some embodiments of the present invention, the molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1-2.
[0008] According to some embodiments of the present invention, the molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1.
[0009] According to some embodiments of the present invention, the crystallization reaction temperature is 160°C.
[0010] According to some embodiments of the present invention, the crystallization reaction time is 48 h.
[0011] According to some embodiments of the present invention, the drying temperature of the MOFs material precipitate is 70° C., and the drying time is 12 h.
[0012] According to some embodiments of the present invention, washing and centrifuging the MOFs material precipitate comprises: Add 50 ml of anhydrous ethanol to wash and centrifuge the MOFs material precipitate to remove residual organic matter precipitated on the surface of the MOFs material precipitate; 50 ml of deionized water was added to wash and centrifuge the MOFs material precipitate to remove the anhydrous ethanol precipitated on the surface of the MOFs material precipitate.
[0013] On the other hand, an embodiment of the present invention provides the use of the surface hydroxylated flexible MOFs material in storing natural gas.
[0014] According to some embodiments of the present invention, the reaction temperature of the surface hydroxylated flexible MOFs material for storing natural gas is 0-4° C. and the pressure is 0-8 MPa.
[0015] The embodiments of the present invention have at least the following beneficial effects: The embodiment of the present application proposes a method for preparing a surface hydroxylated flexible MOFs material, which adopts a water / solvent thermal synthesis method, screens the reaction ratio, reaction temperature and reaction time, and proposes specific feasible synthesis steps; the two major steps of MOFs material basic skeleton synthesis and surface hydroxylation treatment are combined into one step, and hydroxylation is directly performed during the synthesis process to simplify the production process; and there is only one hydroxyl group on the organic ligand used, and the number of hydroxyl groups and hydroxyl sites are determined and evenly distributed, so as to avoid the possibility of clogging the pores due to excessive number of hydroxyl groups, resulting in reduced wet storage effect. The process of synthesizing MOFs materials is optimized to prepare MOFs materials with good crystallinity, thereby improving their breathing effect and wet storage performance. The surface hydroxylated flexible MOFs material is a metal organic framework material with a high specific surface area, adjustable pore structure and rich hydroxyl groups on the surface; its flexible characteristics enable it to undergo structural changes under external stimuli (such as pressure, temperature, gas adsorption, etc.), and surface hydroxylation enhances its hydrophilicity and chemical reactivity. The operation is safe, the synthesis time is short, the energy consumption is low, and the crystallization process of MOFs materials is more effectively promoted, thereby obtaining a higher quality crystal structure and improving the product yield and purity. Due to its unique structure and surface characteristics, the surface hydroxylated flexible MOFs material improves its performance and expands its application range. It regulates heat migration through the breathing effect induced by methane adsorption, reasonably solves the technical bottleneck of thermal effects in practical applications, and realizes efficient storage and transportation of natural gas under mild conditions.
[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 This is a flow chart of a method for preparing a surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 2 A schematic diagram of the synthesis route of the surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 3IR spectra of the surface hydroxylated flexible MOFs material and the flexible MOFs material according to the embodiment of the present invention; Figure 4 This is a flow chart of washing and centrifuging a MOFs material precipitate in a method for preparing a surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 5 A bar graph showing the effect of the ratio of reactants on the yield and purity of the product in the method for preparing the surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 6 A bar graph showing the effect of reaction time on product yield and purity in the method for preparing a surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 7 A bar graph showing the effect of reaction temperature on product yield and purity in the method for preparing a surface hydroxylated flexible MOFs material according to an embodiment of the present invention; Figure 8 It is a line graph showing the influence of temperature and pressure on the adsorption amount in the application of the surface hydroxylated flexible MOFs material according to the embodiment of the present invention. DETAILED DESCRIPTION
[0018] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0019] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0020] In the description of the present invention, "several" means one or more, "multiple" means more than two, greater than, less than, and exceeding are understood as not including the number itself, and "above", "below", and "within" are understood as including the number itself. If there is a description of "first", "second", etc., it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0021] In the description of the present invention, unless otherwise clearly defined, words such as “set”, “install”, “connect” and “connected” should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above words in the present invention based on the specific content of the technical solution.
[0022] The technical solution of the present invention is described in detail below through the accompanying drawings and specific embodiments.
[0023] See also Figure 1 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material, which mainly includes steps S101 to S106: S101, dissolving 5-10 mmol of aluminum nitrate nonahydrate in 30 ml of deionized water, and stirring until completely dissolved to obtain an inorganic aluminum salt solution; S102, dissolving 5-10 mmol 2-hydroxyterephthalic acid in 30 ml N,N-dimethylformamide (DMF), and stirring until completely dissolved to obtain an organic ligand solution; S103, dripping the organic ligand solution into the aluminum salt inorganic solution to form a mixed solution, transferring the mixed solution into a high-pressure reactor, and performing a crystallization reaction at 130-220° C. for 24-72 h; S104, after the temperature of the high-pressure reactor is cooled to room temperature, centrifuging to obtain a MOFs material precipitate; S105, washing and centrifuging the MOFs material precipitate to remove residual organic matter and anhydrous ethanol precipitated on the surface of the MOFs material precipitate; S106. Place the MOFs material precipitate in a constant temperature drying oven and dry it at 60-80°C for 10-14 hours to obtain a surface hydroxylated flexible MOFs material.
[0024] The embodiment of the present application proposes a method for preparing a surface hydroxylated flexible MOFs material, which combines the two major steps of MOFs material basic skeleton synthesis and surface hydroxylation treatment into one step, directly hydroxylating during the synthesis process, simplifying the production process; and the organic ligand used has only one hydroxyl group, the number of hydroxyl groups and hydroxyl sites are determined and evenly distributed, avoiding the possibility of clogging the pores due to excessive hydroxyl numbers, resulting in reduced wet storage effect, and improving product yield and purity. The surface hydroxylated flexible MOFs material is a metal organic framework material with a high specific surface area, adjustable pore structure and rich hydroxyl groups on the surface; its flexible properties enable it to undergo structural changes under external stimuli (such as pressure, temperature, gas adsorption, etc.), and surface hydroxylation enhances its hydrophilicity and chemical reactivity. The surface hydroxylated flexible MOFs material has a wide range of application prospects in the field of natural gas storage due to its unique structure and surface characteristics, which improves its performance and expands its application range.
[0025] See also Figure 2 The chemical formula of the surface hydroxylated flexible MOFs material is MIL-53(Al)-OH, the chemical formula of the aluminum nitrate nonahydrate is Al(NO3)39H2O, and the chemical formula of the 2-hydroxyterephthalic acid is H2BDC-OH.
[0026] See also Figure 3 Using the information provided by infrared absorption spectroscopy, it can be seen that the surface hydroxylated flexible MOFs material (MIL-53(Al)-OH) has a successful hydroxyl loading and has the same structure as the material before hydroxylation (MIL-53(Al)); the specific surface area of MIL-53(Al)-OH is measured to be 558.97m 2 / g, micropore specific surface area is 463.92m 2 / g, pore volume is 0.33cm 3 / g. The surface hydroxylated flexible MOFs material is a metal organic framework material with high specific surface area, adjustable pore structure and rich hydroxyl groups on the surface. The surface hydroxylated flexible MOFs material prepared by this preparation method has higher intensity at the corresponding characteristic diffraction peak and better crystallinity, indicating that the synthetic method adopted can effectively promote the crystallization process of MOFs material, thereby obtaining a higher quality crystal structure.
[0027] In some specific embodiments of the present invention, the molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1-2.
[0028] In some specific embodiments of the present invention, the molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1.
[0029] In some specific embodiments of the present invention, the crystallization reaction temperature is 160° C. and the crystallization reaction time is 48 h.
[0030] In some specific embodiments of the present invention, the drying temperature of the MOFs material precipitate in step S106 is 70° C. and the drying time is 12 h.
[0031] See also Figure 4 In the above step S105, the MOFs material precipitate is washed and centrifuged, comprising: S201, adding 50 ml of anhydrous ethanol, washing and centrifuging the MOFs material precipitate to remove residual organic matter precipitated on the surface of the MOFs material precipitate; S202, adding 50 ml of deionized water, washing and centrifuging the MOFs material precipitate to remove the anhydrous ethanol precipitated on the surface of the MOFs material precipitate.
[0032] Example 1 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid used in this embodiment is 2:1, that is, aluminum nitrate nonahydrate is 10 mmol and 2-hydroxyterephthalic acid is 5 mmol. The preparation steps are basically the same as the above steps S101 to S106.
[0033] Example 2 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid used in this embodiment is 1.5:1, that is, aluminum nitrate nonahydrate is 7.5 mmol and 2-hydroxyterephthalic acid is 5 mmol. The preparation steps are basically the same as the above steps S101 to S106.
[0034] Example 3 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid used in this embodiment is 1:1, that is, the aluminum nitrate nonahydrate is 5 mmol and the 2-hydroxyterephthalic acid is 5 mmol. The preparation steps are basically the same as the above steps S101 to S106.
[0035] Example 4 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid used in this embodiment is 1:2, that is, aluminum nitrate nonahydrate is 5 mmol and 2-hydroxyterephthalic acid is 10 mmol. The preparation steps are basically the same as the above steps S101 to S106.
[0036] See also Figure 5 The ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid was changed to four reactant ratios of 2:1, 1.5:1, 1:1, and 0.5:1, respectively. The process was optimized according to the product yield and purity. It can be seen that when the molar ratio of aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1, the yield and purity of the prepared surface hydroxylated flexible MOFs material are higher.
[0037] Example 5 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 24 hours, and the preparation steps are basically the same as the above-mentioned steps S101 to S106.
[0038] Example 6 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 36 hours, and the preparation steps are basically the same as the above-mentioned steps S101 to S106.
[0039] Example 7 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 48 hours, and the preparation steps are basically the same as the above-mentioned steps S101 to S106.
[0040] See also Figure 6 By changing the reaction time to 24 h, 36 h and 48 h, the process was optimized according to the product yield and purity. It can be seen that when the crystallization reaction time is 48 h, the yield and purity of the prepared surface hydroxylated flexible MOFs material are higher.
[0041] Example 8 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction temperature of this embodiment is 130° C., and the preparation steps are basically the same as the above-mentioned steps S101 to S106.
[0042] Example 9 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 160° C., and the preparation steps are basically the same as the above steps S101 to S106.
[0043] Example 10 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 190° C., and the preparation steps are basically the same as the above steps S101 to S106.
[0044] Embodiment 11 This embodiment provides a method for preparing a surface hydroxylated flexible MOFs material. The crystallization reaction time of this embodiment is 220° C., and the preparation steps are basically the same as the above-mentioned steps S101 to S106.
[0045] See also Figure 7 By changing the reaction temperature to four temperature points of 130 ℃, 160 ℃, 190 ℃ and 220 ℃, the process was optimized according to the product yield and purity; it can be seen that when the crystallization reaction temperature is 160 ℃, the yield and purity of the prepared surface hydroxylated flexible MOFs material are higher.
[0046] According to Example 1 to Example 11, the present invention adopts a water / solvent thermal synthesis method, proposes specific feasible synthesis steps, screens the reaction ratio, reaction temperature and reaction time, and optimizes the process of synthesizing MOFs materials, thereby preparing materials with better crystallinity and improving their breathing effect and wet storage performance. The operation is safe, the synthesis time is short, the energy consumption is low, and the crystallization process of MOFs materials is more effectively promoted, thereby obtaining a higher quality crystal structure and improving the product yield and purity. By screening the appropriate reaction ratio, reaction temperature and reaction time, a preparation method with high yield and purity of surface hydroxylated flexible MOFs materials is obtained, and the main steps are as follows: 1. Dissolve 5 mmol aluminum nitrate nonahydrate in 30 ml deionized water and stir until completely dissolved to obtain an inorganic aluminum salt solution; 2. Dissolve 5 mmol of 2-hydroxyterephthalic acid in 30 ml of N,N-dimethylformamide and stir until completely dissolved to obtain an organic ligand solution; 3. Drop the organic ligand solution into the aluminum salt inorganic solution to form a mixed solution, transfer the mixed solution to a high-pressure reactor, and perform a crystallization reaction at 160°C for 48 hours; 4. After the temperature of the high-pressure reactor is cooled to room temperature, the MOFs material precipitate is obtained by centrifugation; 5. Wash and centrifuge the MOFs material precipitate to remove residual organic matter and anhydrous ethanol precipitated on the surface of the MOFs material precipitate; 6. Place the MOFs material precipitate in a constant temperature drying oven and dry it at 70°C for 12 h to obtain a surface hydroxylated flexible MOFs material.
[0047] Example 12 This example provides an experiment on natural gas storage using surface hydroxylated flexible MOFs materials. The specific steps of the experiment are: The surface hydroxylated flexible MOFs material is titrated with deionized water, so that the MOFs material pre-absorbs water and the water content Rw is 2.0, where the water content Rw is the mass of the pre-absorbed water divided by the mass of the dry material; Then, the surface hydroxylated flexible MOFs material that has been pre-absorbed with water is placed in a visual reactor, and the reactor is kept at 0-4 °C, and methane is introduced at a pressure of 0-8 MPa. Methane is continuously introduced every 1 hour to form a reaction system for wet storage of methane. Calculate the methane consumption. Use the gas state equation to calculate the amount of methane before and after the reaction. Subtract the two to get the methane consumption.
[0048] The gas state equation calculation formula is: Where P0 is the initial injection pressure of methane, P t is the pressure in the reactor at reaction time t, T is the temperature in the reactor, V t is the volume of gas in the reactor, Z0 is the compression factor at the initial pressure, Z is the compression factor at reaction time t, and R is the gas constant.
[0049] See also Figure 8 By changing the reaction temperature, the adsorption was carried out at three points: 0℃, 2℃ and 4℃, and at different pressures of 0-8MPa. It can be seen that when the reaction temperature is 0℃ and the pressure is 7.8, the methane adsorption amount is higher.
[0050] Therefore, the present invention proposes the application of a flexible MOFs material with hydroxylated surface, which regulates the heat transfer of the system through the methane adsorption-induced breathing effect, reasonably solves the technical bottleneck of thermal effect in practical applications, improves the specific surface area, stability and gas storage capacity of the MOFs material, and realizes the efficient storage of methane. It can be used for the storage and transportation of natural gas in remote areas and areas that are not suitable for pipeline collection and transportation, and realizes the efficient storage and transportation of natural gas under mild conditions. It has broad application prospects in the field of natural gas storage and transportation.
[0051] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a surface hydroxylated flexible MOFs material, characterized in that: include: Dissolve 5-10 mmol aluminum nitrate nonahydrate in 30 ml deionized water and stir until completely dissolved to obtain an inorganic aluminum salt solution; Dissolve 5-10 mmol 2-hydroxyterephthalic acid in 30 ml N,N-dimethylformamide and stir until completely dissolved to obtain an organic ligand solution; The organic ligand solution is dripped into the aluminum salt inorganic solution to form a mixed solution, and the mixed solution is transferred to a high-pressure reactor to perform a crystallization reaction at 130-220° C. for 24-72 h; After the temperature of the high-pressure reactor is cooled to room temperature, the MOFs material precipitate is obtained by centrifugation in a centrifuge; Washing and centrifuging the MOFs material precipitate to remove residual organic matter and anhydrous ethanol precipitated on the surface of the MOFs material precipitate; The MOFs material precipitate is placed in a constant temperature drying oven and dried at 60-80° C. for 10-14 h to obtain a surface hydroxylated flexible MOFs material.
2. The method for preparing the surface hydroxylated flexible MOFs material according to claim 1, characterized in that: The chemical formula of the surface hydroxylated flexible MOFs material is MIL-53(Al)-OH, the chemical formula of the aluminum nitrate nonahydrate is Al(NO3)39H2O, and the chemical formula of the 2-hydroxyterephthalic acid is H2BDC-OH.
3. The method for preparing the surface hydroxylated flexible MOFs material according to claim 1, characterized in that: The molar ratio of the aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:1-2.
4. The method for preparing the surface hydroxylated flexible MOFs material according to claim 1, characterized in that: The molar ratio of the aluminum nitrate nonahydrate to 2-hydroxyterephthalic acid is 1:
1.
5. The method for preparing the surface hydroxylated flexible MOFs material according to claim 1, characterized in that: The crystallization reaction temperature was 160 °C.
6. The method for preparing the surface hydroxylated flexible MOFs material according to claim 5, characterized in that: The crystallization reaction time was 48 h.
7. The method for preparing the surface hydroxylated flexible MOFs material according to claim 6, characterized in that: The drying temperature of the MOFs material precipitate is 70° C. and the drying time is 12 h.
8. The method for preparing a surface hydroxylated flexible MOFs material according to claim 1, characterized in that: The washing and centrifuging of the MOFs material precipitate comprises: Add 50 ml of anhydrous ethanol to wash and centrifuge the MOFs material precipitate to remove residual organic matter precipitated on the surface of the MOFs material precipitate; 50 ml of deionized water was added to wash and centrifuge the MOFs material precipitate to remove the anhydrous ethanol precipitated on the surface of the MOFs material precipitate.
9. Use of a surface hydroxylated flexible MOFs material prepared by the method for preparing a surface hydroxylated flexible MOFs material according to any one of claims 1 to 8 in storing natural gas.
10. The use of the surface hydroxylated flexible MOFs material in natural gas storage according to claim 9, characterized in that: The reaction temperature of the surface hydroxylated flexible MOFs material for storing natural gas is 0-4° C. and the pressure is 0-8 MPa.
Citation Information
Patent Citations
Nanoscale aluminium-based metal-organic framework structure material and preparation method thereof
CN104497032A
Preparation method of hydroxyl modified metal organic framework material fluorescent probe, and fluoride detection application of fluorescent probe
CN111978557A
Application of MIL-53 aluminum-based metal organic framework material as stabilizer
CN115322060A
Preparation method of bifunctional flexible metal organic framework material for ammonia storage
CN119060352A
Method of producing microporous aluminum terephthalate
RU2718676C1